2021
DOI: 10.3390/nano11020459
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure of Porous Si and Anodic SiO2 Surface Passivation for Improved Efficiency Porous Si Solar Cells

Abstract: The photovoltaic effect in the anodic formation of silicon dioxide (SiO2) on porous silicon (PS) surfaces was investigated toward developing a potential passivation technique to achieve high efficiency nanostructured Si solar cells. The PS layers were prepared by electrochemical anodization in hydrofluoric acid (HF) containing electrolyte. An anodic SiO2 layer was formed on the PS surface via a bottom-up anodization mechanism in HCl/H2O solution at room temperature. The thickness of the oxide layer for surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The properties have consequently been determined by the finally achieved pore sizes and depths. The application areas are very wide, and include sensors, catalysts, solar cells, and charge storages [8][9][10][11][12][13][14][15][16][17]. For sensors, Ramírez-González et al controlled the thickness of the PS layer and tested ethanol-sensing performance by measuring conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties have consequently been determined by the finally achieved pore sizes and depths. The application areas are very wide, and include sensors, catalysts, solar cells, and charge storages [8][9][10][11][12][13][14][15][16][17]. For sensors, Ramírez-González et al controlled the thickness of the PS layer and tested ethanol-sensing performance by measuring conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the nanocomposites showed an excellent catalytic performance for the reduction of 4-nitrophenol to 4-aminophenol by NaBH 4 . For solar cells, Sundarapura et al prepared an anodic SiO 2 layer on a PS surface, and demonstrated that the solar-cell efficiency was significantly improved [13]. For energy storage, Ortaboy et al synthesized MnO x -decorated carbonized porous Si nanowire, and showed that the PS nanowire-based pseudocapacitor electrode had a specific capacitance of 635 F g −1 ,…”
Section: Introductionmentioning
confidence: 99%
“…Anodization is a commonly used name for electrochemical oxidation of metals [1][2][3], their alloys [4,5] and semiconductors [6][7][8] under either galvanostatic or potentiostatic conditions in a two-electrode setup since the oxidized material plays a role of an anode. Originally, the major application of anodic oxidation was corrosion protection of lightweight aluminum alloys [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Results show that the anodization process coupled with the heat treatment provides significant corrosion protection to the SS and the welds. Furthermore, the proposed methodology has distinct advantages of being simple, safe, low-cost, and versatile, making it highly promising in numerous fields [33][34][35].…”
Section: Introductionmentioning
confidence: 99%